Capim-paiaguás submetido a doses de cinza vegetal e disponibilidades hídricas - Bezerra, Maria Débora Loiola (2018)
The incorporation of vegetable ash into the soil can increase water retention in the soil and intensify forage production even under low water availability. The objective of this study was to evaluate the development and production of paiaguas grass (Urochloa brizantha) submitted to doses of vegetable ash and soil water availability. The experiment was carried out in a greenhouse using a randomized block design in a 5x5 fractional factorial scheme, corresponding to five doses of plant ash (0, 8, 16, 24 and 32 g dm-3 ) and five soil water availability (4; 8; 16; 32; 64 kPa) with four replicates. The experimental design was based on the modified central compound in which 13 combinations of doses of vegetal ash (g dm-3 ) and soil water availability (kPa) were studied: 0-4; 0-16; 0-64; 8-8; 8-32; 16-4; 16-16; 16-64; 24-8; 24- 32; 32-4; 32-16; 32-64. Each experimental unit was composed of a vessel made of PVC pipes, polyvinyl chloride, of 300 mm height by 200 mm diameter, with soil volume of 8.7 dm3 with five paiaguas grass plants. In the interval of 30 days, three cuts were made in the aerial part of the plants, being evaluated the phytometric characteristics: leaf angle, stem diameter+sheath, plant height, number of leaves, number of tillers, ratio leaf/stem+sheath, leaf area and root volume; productive: dry mass of leaves, stems+sheath, shoot and root (this in the last cut); nutritional status of the plant: chlorophyll index; (soil pH before sowing and with each cut), total water consumption and water use efficiency by grass. The results were submitted to analysis of variance and regression, both up to 5% probability of error, through the SISVAR program, and when there was a significant interaction among the treatments the results were analyzed through the SAS (System for Windows) statistical program. The best results of development and dry mass production of paiaguás grass were found with incorporation of vegetable ash in the soil. The high soil water tension influences the phytometric characteristics and reduces the dry mass production of the grass. The incorporation of vegetable ash into the soil increases the pH and water retention of the Oxisol.